2021
DOI: 10.1002/mgg3.1670
|View full text |Cite
|
Sign up to set email alerts
|

Severe brain calcification and migraine headache caused by SLC20A2 and PDGFRB heterozygous mutations in a five‐year‐old Chinese girl

Abstract: Primary familial brain calcification (PFBC) is a rare inheritable neurodegenerative disease mainly characterized by symmetrical calcification in the basal ganglia, thalamus, cerebellum, and brainstem (Wang et al., 2012). Patients with PFBC may experience movement disorders, cognitive impairment, psychiatric signs, or other associated manifestations with diverse severity and variable onset age or may be asymptomatic throughout their lives (Nicolas et al., 2015;Wang et al., 2015).PFBC can be transmitted in an au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This is consistent with our results, with variants in NAA60 affecting SLC20A2 PM localization and cellular P i homeostasis. Moreover, a complex PFBC genotype-phenotype spectrum emerges as cases that involve dose-dependent variants have been associated with a severe clinical and neuroimaging spectrum 32 . SLC20A2 heterozygous mutations are associated with the adult-onset phenotype, while homozygous SLC20A2 variants resulted in severe phenotype including growth retardation, microcephaly, and convulsion 33 , similar to some of the NAA60 variants reported here.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our results, with variants in NAA60 affecting SLC20A2 PM localization and cellular P i homeostasis. Moreover, a complex PFBC genotype-phenotype spectrum emerges as cases that involve dose-dependent variants have been associated with a severe clinical and neuroimaging spectrum 32 . SLC20A2 heterozygous mutations are associated with the adult-onset phenotype, while homozygous SLC20A2 variants resulted in severe phenotype including growth retardation, microcephaly, and convulsion 33 , similar to some of the NAA60 variants reported here.…”
Section: Discussionmentioning
confidence: 99%
“…The first type of mutation is located in extracellular Ig-like domains (D1–D5), causing the receptor to lose its ability to bind to PDGF-BB, such as R106P (D1), P154S (D2), R226C (D3) ( Sun et al, 2021 ; Lenglez et al, 2022 ), and R334Q (D4). The R334 is highly evolutionarily conserved in mammalian species.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing this information, we found that patients with dysphagia, verbal impairment, cognitive impairment, and dyskinesia as primary symptoms were mainly middle-aged and elderly ( 14 18 ). Conversely, patients with headache as the main clinical symptom are generally younger ( 10 , 19 ). Therefore, we hypothesize that earlier age of onset is associated with increased risk of headache and migraine, and that other corresponding symptoms may then develop with age.…”
Section: Discussionmentioning
confidence: 99%